Jephtha, a Sacred Oratorio: In Score, Composed in the Year 1751 - Handel, George Frideric 1685-1759; Morell, Thomas 1703-1784 (London Arnold, 1792)
The story revolves around Jephtha's rash promise to the Almighty that if he is victorious, he will sacrifice the first creature he meets on his return. He is met by his beloved daughter Iphis. However, an angel intervenes to stop the sacrifice, and Iphis only needs to dedicate her life to the Lord. This is an unusual interpretation of the Bible story, although one which has been current since the Middle Ages. The more common interpretation is that Jephthah chooses to sacrifice his daughter, but a short reprieve is arranged, after which Iphis dutifully returns and is killed.
The oratorio Jephtha (HWV 70) has an English language libretto by the Rev. Thomas Morell, based on the story of Jephtha in Judges (Chapter 11) and Jephthes, sive Votum (Jeptha, or the Vow) (1554) by George Buchanan. Whilst writing Jephtha, Handel was increasingly troubled by his gradual loss of sight, and this proved to be his last oratorio. In the autograph score, at the end of the chorus "How dark, O Lord, are thy decrees" he wrote "Reached here on 13 February 1751, unable to go on owing to weakening of the sight of my left eye."
Ex libris Dr. Arnold, 1842 & William Pole, 1895 (manuscript)
Keywords: 18th Century (1701-1800); Oratorio; Religion; London (United Kingdom)